Menelusuri Tingkat Pengetahuan Kesehatan Reproduksi Remaja : Studi di Kabupaten Sijunjung - Yessi Kartalina; Teguh Widodo (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2020)
Adolesence, in physchological term is called transitition period. They are seeking self-identity. Most of them start to attract to the opposite sex. Then they try to approach acquaintances to dating and even have sexual intercourse. On the other hand, limited sexual knowledge coupled with the souls of adolescents who are still out of control, their emotions can lead to promiscuity which is considered bad in Eastern customary arrangements. On the health side, promiscuity which leads to unwanted pregnancies is thought to increase the risk of death for mothers and their babies. This study tries to trace the level of knowledge of reproductive health among adolescents and to obtain information on the extent of their attitudes and behavior towards sexuality towards the opposite sex. The data sample collection is purposive towards 800 junior high and high school students who have a Youth Information and Counseling Center (PIK-R). The analysis was carried out descriptively by looking at the frequency distribution. The results showed that adolescents' knowledge of fertility was still low (2.5%) but they knew (63%) that sexual intercourse can lead to pregnancy. Information about reproductive health obtained by adolescents mostly from electronic media and health workers (82%). The recommendations of this study emphasize the intensity of family planning officers and school teachers in providing knowledge of reproductive health periodically to new students entering school.